Identifikasi Naskah dan Klasifikasi Corrupt Manuskrip Mushaf al-Qur’an Koleksi Perpustakaan Pondok Pesantren Tebuireng - Adrika Fithrotul Aini (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This study focused on the Qur’anic mushaf manuscript, the heritage collection of KH. Hasyim Asy'ari, stored in the library of Tebuireng pesantren. In this Pesantren, there are many collections of manuscripts, but this Qur’anic manuscript is never discussed bythe researchers who scrutinize KH. Hasyim Asy’ari’s collection works. The present study had three stages, namely identification of manuscript, criticism of corrupt texts, and the form of scholia manuscript. The purposes of this study were to explain the identity of the manuscript and classify the corrupt and scholia forms that occurred in the Qur'anic manuscript at Tebuireng Pesantren.The method used was the criticism of the texts through the inventory of all faults that occurred in the copying based on the Qur'anic manuscript that had been in tashih. This study found out that (1) the manuscript of the Qur’anicmushaf, the heritage collection of KH. Hasyim Asy'ari, had many mistakes in the process of copying. Frequent mistakes lied in punctuation errors, dots in letters, excess letters, or lack of letters; and (2) The Scholia manuscript form of the Qur’anicmushaf, the heritage of KH. Hasyim Asy'ari, was used to give clarification on the mistakes that occurred in the texts. This is different from the scholia in the manuscripts of the Quran in Indonesia, which is commonly used for maqra' and the Juz